The concept of Rusydi Ahmad Thu'aimah in the Arabic Textbook MI Ministry of Religious Affairs / Konsep Rusydi Ahmad Thu'aimah dalam Buku Teks Bahasa Arab MI Kementerian Agama - Sugirma Sugirma; Dian Risky Amalia; Nurhadi Nurhadi; Wildana Wargadinata; Siti Sulaikho (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
The Arabic textbook of MI Ministry of Religious Affairs became a national textbook and became a guide for other supporting books such as LKS at the Madrasah level. The quality and effectiveness of the book "Kitābu at-Ṭālib al-Lughah al 'Arabiyyah" requires validation in its implementation in MI as a student need. Rusydi Ahmad Thu'aimah, a world-caliber Arabic expert, has categories and concepts about textbooks that will be synchronized with grade 3 textbooks MI Ministry of Religious Affairs.This type of research is Content Analysis which focuses on the material of the textbook "Kitābu at-Ṭālib al-Lughah al-'Arabiyyah" on the characteristics of the concept of Rushdi Ahmad Thu'aimah. The result of the study was the book "Kitābu at-Ṭālib al-Lughah al-'Arabiyyah" in accordance with the 5 standards set by Rushdi Ahamad Thu'aimah, includes validity standards that refer to KMA number 183 of 2019, urgent standards have covered cognitive, affective and psychomotor stages, talent interest standards with image stimuli and fun game play, learning capability standards starting from simple stages to difficult stages, and natural standards, the material presented contains ecoliteracy and contemporary values that are in sync with student life. Researchers then to measure the effectiveness of this book in the learning process in the field and further analyze the perceived benefits of this student book, when applied in their schools and the development of effective learning strategies.Abstrak: Buku ajar bahasa Arab MI Kementerian Agama menjadi buku ajar nasional dan menjadi pedoman bagi buku penunjang lainnya seperti LKS tingkat Madrasah. Kualitas dan keefektifan kitab “Kitabu at-Ṭālib al-Lughah al ‘Arabiyyah” memerlukan validasi dalam penerapannya di MI sebagai kebutuhan siswa. Rusydi Ahmad Thu'aimah, pakar bahasa Arab berkaliber dunia, mempunyai kategori dan konsep tentang buku ajar yang akan disinkronkan dengan buku ajar kelas 3 MI Kementerian Agama. Jenis penelitian ini adalah Content Analysis yang fokus pada materi buku ajar “Kitabu at-Ṭālib al-Lughah al-'Arabiyyah" tentang ciri-ciri konsep Rusydi Ahmad Thu'aimah. Hasil penelitian adalah kitab “Kitābu at-Ṭālib al-Lughah al-’Arabiyyah” sesuai dengan 5 standar yang ditetapkan oleh Rushdi Ahamad Thu’aimah, meliputi standar keabsahan yang mengacu pada KMA nomor 183 tahun 2019, standar mendesak mempunyai meliputi tahapan kognitif, afektif dan psikomotorik, standar minat bakat dengan rangsangan gambar dan permainan yang menyenangkan, standar kemampuan belajar mulai dari tahap sederhana sampai tahap sulit, dan standar alam, materi yang disampaikan mengandung ecoliteracy dan nilai-nilai kekinian yang selaras dengan kehidupan siswa. Peneliti kemudian mengukur keefektifan buku ini dalam proses pembelajaran di lapangan dan menganalisis lebih lanjut manfaat yang dirasakan dari buku siswa ini, bila diterapkan di sekolahnya serta pengembangan strategi pembelajaran yang efektif.